Fabrication of electrospun adsorptive membranes for lithium extraction from dilute aqueous solutions - Lim, Xin Yi (Nanyang Technological University, 2024)
The demand for lithium has continued to grow over the years due to its growing use in lithium batteries and electric vehicles, with a 2020 study suggesting that the annual demand for lithium is projected to reach >1,000,000 tonnes by 2030. The precious metal can be found both on land and in the ocean. While lithium on earth has been extensively mined, the ocean is still a relatively untapped but large source of lithium. Consequently, much research has been done into potential methods of seawater lithium extraction — including conventional adsorption, adsorptive membranes, liquid-liquid extraction and electrochemical methods.